Postmortem interval estimation in cats using vitreous potassium: Development of a regression model - F. Almas; M. Pradeep; A. J. George; B. D. Krishna; S. S. Devi; R. Rajasekhar; N.K. Mansoor (Journal of Veterinary and Animal Sciences, 2025)
Accurate postmortem interval (PMI) estimation is critical in forensic investigations and in vetero-legal procedures. Even though vitreous humour potassium concentration has been studied previously in humans and dogs to estimate PMI, studies on cats are scanty. The present study investigated vitreous potassium concentrations in cat carcasses  different PMI and its potential for estimating PMI in cats. The cats with known PMI brought for post-mortem examination at the Department of Veterinary Pathology, College of Veterinary and Animal Sciences, Pookode, Wayanad formed the study material. Vitreous humour was collected from 12 cat carcasses with PMIs ranging from one to fifty-two hours. Data including the age and sex of the cats and ambient temperature at the time of collection were recorded. Potassium concentration was quantified from clear supernatant collected after centrifugation of vitreous humour using the ionselective electrode method. Statistical analysis revealed a strong positive correlation between potassium concentration and PMI (r 0.919, p